Analisis Efisiensi Sistem Turbocharger pada Engine PLTMG 20 MW Berdasarkan Konsumsi Udara - Sepfitrah; Rinaldi; Febrianton, Adi; Pranoto, Siswo; Ferial, Arios (SURYA TEKNIKA, 2022)
Turbocharging system efficiency is a comparison between turbocharging efficiency and turbocharger efficiency. This study analyzes the performance of the ABB 140 and TCR 18 turbochargers on two JGS 620 series F111 gas engines for 3000 hours of operation. The analysis will be carried out based on the specific airflow consumption of the JGS 620 series F111 gas engine. The specific air flow consumption is obtained based on calculations, the ABB A140 turbocharger consumes an average of 0.2% more air than the TCR 18 turbocharger. This condition results in a higher output power on engine 2 on average of 2516.84 kW, compared to the output power engine 1 on average of 2402.72 kW. Based on the calculation of the conduction ratio, the average air consumption on engine 2 is less than engine 1 by 0.41%. The turbocharging efficiency value on the turbine engine 2 side is disrupted at 1700 and 2500 hours of operation. This is due to the disturbance on the turbocharger compressor side of the incoming airflow. The efficiency of the turbocharging system on engine 1 has a value of 79.77%, while on engine 2 it is 77.99%.